90TiP FRAIL-IMMUNE: A multicenter, prospective, single arm phase II of the combination of durvalumab with carboplatin and paclitaxel as first-line treatment in patients with recurrent/metastatic squamous cell carcinoma of the head and neck not eligible to standard chemotherapy (GORTEC 2018-03). (15th December 2019) - Fayette, J
Abstract: Background: One third of patients with (R/M SCCHN) are not eligible to receive the standard first-line chemotherapy EXTREME (cisplatin, fluorouracile and cetuximab). In this population, the weekly scheme of carboplatin-paclitaxel demonstrated clinical efficacy an overall survival (OS) of 4.9-12.8 months and a response rate of 20-52%. In a study conducted in our center, patients ineligible to EXTREME due to performance status (PS) 2 or other reasons (excluding PS2) reached a median OS of 3.6 months and 11.5 months, respectively. Trial Design: A prospective, multicenter, single-arm phase II trial to study the efficacy and safety of durvalumab (anti-PD-L1) combined with carboplatin-paclitaxel in patients with R/M SCCHN ineligible to cisplatin. A first cohort of patients (n = 64) with PS0-1 will be accrued, then a cohort of patients with PS2 (n = 38) if results of the cohort PS0-1 are positive. Patients will receive four 28-day cycles (carboplatin AUC2 and paclitaxel 80mg/m², D1, D8, D15) with 4-weekly infusions of 1500mg durvalumab (pursued for a maximum of 12 months). An initial safety run-in step with predefined stopping rules is being conducted in the first 6 patients of the cohort PS0-1. The primary objective will be to determine the efficacy (12-month OS rate) of the combination. The treatment will be considered for further investigations, if at least 38 successes and 10 successes are observed in cohorts PS0-1 and PS2, respectively. Secondary endpoints will also be investigated: progression-free survival, time-to-treatment failure, OS, response rates, quality of life (QLQ-C30 and QLQ-H&N35) and tolerance profile of the combination. Radiological endpoints will be evaluated using the RECIST version 1.1. Translational objectives will be to study blood and tumor markers (expression of immune checkpoints, immune infiltrate and molecular alterations) as predictive and prognostic factors of efficacy. As of Oct 2 nd 2019, a total of 5 patients has been accrued in the safety run-in step. Clinical trial identification: NCT0372967. Legal entity responsible for the study: Centre Léon Berard. Funding: AstraZeneca. Disclosure: J. Fayette: Honoraria (self): Bristol-Myers Squibb; Honoraria (self), Research grant / Funding (self): AstraZeneca; Honoraria (self): MSD; Honoraria (self): Innate Pharma; Honoraria (self): Merck; Honoraria (self): Rakuten; Honoraria (self): Biogen.